Short-Circuit Disturbance and Distribution Network Protection Electric Power System in Human Resources Development Center for Oil and Gas - Handy Agung (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2025)
The power system is a very vital part of the industry, serving as the source of electrical energy up to the distribution of electric power, which must be protected against various types of disturbances that may affect the equipment in use. Power system protection is the protection provided to electrical equipment installed in a system against abnormal operating conditions of the system itself. These abnormal conditions include short-circuit faults, overload faults, and overvoltage disturbances. Breaking capacity, or the maximum interrupting capacity, is the highest short-circuit current value that a circuit breaker can withstand without sustaining damage.